Teacher Learning Management: Investigating Biology Teachers’ TPACK to Conduct Learning During the Covid-19 Outbreak - Juanda, A.; Shidiq, A. S.; Nasrudin, D. (Jurnal Pendidikan IPA Indonesia, 2021)
Adaptation of new habits in many aspects of life, including education, is required amid the COVID-19 outbreak. Many countries, including Indonesia, suddenly implement online learning as a realization of social distancing policies. This sudden change in the learning system has become a challenge for teachers. They must be able to integrate technology, pedagogy, and content knowledge to conduct online learning well. Therefore, this study investigates the readiness of biology teachers to face online learning based on their Technological Pedagogical Content Knowledge (TPACK). The purposive survey method was used by distributing questionnaires and conducting online interviews. The questionnaire consists of 30 statements about the TPACK readiness of biology teachers and ten questions about the online learning process during the COVID-19 outbreak. A total of 121 biology teachers in West Java, Indonesia, participated in this study. The findings indicate that biology teachers have sufficient TPACK skills in implementing online learning. However, their technological capabilities still need to be improved. The flexibility of place and time, availability of learning resources, and increased independence of teachers and students in using technology are the advantages of online biology learning during the COVID-19 outbreak. Meanwhile, the problems faced by teachers include technical connectivity and student honesty in taking exams in the implementation of online learning. The uncertainty of when the pandemic will end makes this study important to carry out for evaluation and potential improvement of online biology learning systems.